Organic Approach of Managing Root-knot Nematode, Meloidogyne incognita in Tomato Nursery under Field conditions (Indian Journal of Nematology, 2025)
The experiment was conducted for the management of root-knot nematode, Meloidogyne incognita infesting tomato nursery with different organic amendments viz., castor cake, groundnut cake, jatropha cake, pongamia cake, neem cake, and farmyard manure (FYM) under field conditions. During two years (2021–2022 and 2022–2023) of field trials in tomato nursery, the highest seed germination was recorded in FYM @ 2.5 tons/ha (91.6%) and the least in the case of pongamia cake @ 2 tons/ha (88.1%). Lowestnematode population (142.9 J2/200 cc soil) was found in the treatment neem cake @ 2 tons/ha as compared to untreated check (348.1 J2/200 cc soil). The same trend was observed for the number of eggs per egg mass, root-knot index, and nematode population in the root system over untreated check; neem cake @ 2 tons/ha showed superior results in this case also. The lowest reproduction factor was recorded in the treatment where neem cake @ 2 tons/ha (21.1 and 23.4 during 2021–2022 and 2022–2023, respectively) was applied, followed by carbofuran 3G @ 2 kg a.i./ha.